PENERAPAN LITERASI DENGAN MEMBACA NYARING UNTUK MENGEMBANGKAN KEMAMPUAN BAHASA ANAK USIA DINI - Kholidah Nasution, Nur (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to describe the implementation of literacy through read-aloud activities in developing language skills in early childhood at Aikmel Integrated Islamic Kindergarten, East Lombok, as well as identifying the supporting and inhibiting factors in its implementation. The research method used is descriptive qualitative. Data were collected through observations, interviews with the school principal, teachers, parents, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions, with data validity checked using observer persistence and triangulation. The results show that the read-aloud activity has been carried out effectively. The preparation stages carried out by the teachers include selecting the storybook, understanding its content, and focusing the children's attention. During the read-aloud activity, the teachers pay attention to seating positions, facial expressions, voice intonation, body movements, and involve the children in the story. After the activity, a discussion is held with the children to evaluate their understanding of the story read to them. The supporting factors for this activity include support from the school principal, enthusiasm from the children, teacher creativity, and cooperation between teachers and parents. The inhibiting factors include limited facilities and infrastructure and a lack of self-confidence among some teachers. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan penerapan literasi dengan membaca nyaring dalam mengembangkan kemampuan bahasa anak usia dini di Taman Kanak-kanak Islam Terpadu Aikmel, Lombok Timur, serta mengidentifikasi faktor pendukung dan penghambat pelaksanaannya. Metode penelitian yang digunakan adalah kualitatif deskriptif. Data dikumpulkan melalui observasi, wawancara dengan kepala sekolah, guru, orang tua, dan dokumentasi. Teknik analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan, dengan pengecekan keabsahan data menggunakan ketekunan pengamat dan triangulasi. Hasil penelitian menunjukkan bahwa kegiatan membaca nyaring telah dilaksanakan dengan baik. Tahapan persiapan yang dilakukan guru meliputi pemilihan buku cerita, pemahaman isi cerita, dan memusatkan perhatian anak. Selama kegiatan membaca nyaring, guru memperhatikan posisi duduk, ekspresi wajah, intonasi suara, gerakan tubuh, serta melibatkan anak dalam cerita. Setelah kegiatan membaca, dilakukan diskusi dengan anak untuk mengevaluasi pemahaman mereka terhadap cerita yang dibacakan. Faktor pendukung kegiatan ini antara lain dukungan kepala sekolah, antusiasme anak, kreativitas guru, dan kerjasama antara guru dan orang tua. Faktor penghambat meliputi keterbatasan sarana dan prasarana serta kurangnya rasa percaya diri pada sebagian guru.